Medical Informatics and Bioinformatics: Integration or Evolution through Scientific Crises? - Maojo, V.; Kulikowski, C. (Methods of Information in Medicine, 2006)
Objectives: To contribute a new perspective on recent investigations into the scientific foundations of medical informatics (MI) and bioinformatics (BI). To support efforts that could generate synergies and new research directions.Methods: MI and BI are compared and contrasted from a philosophy of science perspective. Historical examples from MI and BI are analyzed based on contrasting viewpoints about the evolution of scientific disciplines.Results: Our analysis suggests that the scientific approaches of MI and BI involve different assumptions and foundations, which, together with largely non-overlapping communities of researchers for the two disciplines, have led to different courses of development. We indicate how their respective application domains, medicine, and biology may have contributed to these differences in development.Conclusions: An analysis from the point of view of the philosophy of science is characteristic of established scientific disciplines. From a Kuhnian perspective, both disciplines may be entering a period of scientific crisis, where their foundations are questioned and where new ideas (or paradigm shifts) and a progressive research programme are needed to advance them scientifically. We discuss research directions and trends both supporting and challenging integration of the subdisciplines of MI and BI into a unified field of biomedical informatics (BMI), centered around the evolution of information cybernetics.
Keywords: Medical informatics; bioinformatics; philosophy of science; paradigm shift; scientific crisis; evolution